2011
DOI: 10.1073/pnas.1110703108
|View full text |Cite
|
Sign up to set email alerts
|

Extended surfaces modulate hydrophobic interactions of neighboring solutes

Abstract: Interfaces are a most common motif in complex systems. To understand how the presence of interfaces affects hydrophobic phenomena, we use molecular simulations and theory to study hydration of solutes at interfaces. The solutes range in size from subnanometer to a few nanometers. The interfaces are self-assembled monolayers with a range of chemistries, from hydrophilic to hydrophobic. We show that the driving force for assembly in the vicinity of a hydrophobic surface is weaker than that in bulk water and decr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
224
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(250 citation statements)
references
References 54 publications
19
224
1
Order By: Relevance
“…Our results have implications on interface-mediated self-assembly and suggest that water-mediated electrostatic interactions may play an even more important role at soft aqueous interfaces compared with that in bulk water. These results on ions along with the results of recent studies on hydrophobic interactions at aqueous interfaces (16)(17)(18) provide a framework for understanding and manipulating self-assembly of surfactants, peptides, proteins, and other macromolecules at interfaces.…”
mentioning
confidence: 99%
“…Our results have implications on interface-mediated self-assembly and suggest that water-mediated electrostatic interactions may play an even more important role at soft aqueous interfaces compared with that in bulk water. These results on ions along with the results of recent studies on hydrophobic interactions at aqueous interfaces (16)(17)(18) provide a framework for understanding and manipulating self-assembly of surfactants, peptides, proteins, and other macromolecules at interfaces.…”
mentioning
confidence: 99%
“…Recent simulations have shown that anions at the air-water interface specifically bias the height fluctuations of thermal capillary waves over extended domains. [12][13][14] Given the importance of LR-SIE across many fields, [15][16][17] we deemed pertinent to inquire whether such mechanism is universal and applies to other liquids, 1,18,19 or it is inherent to water. Herein, we report experiments addressing this fundamental question.…”
Section: Introductionmentioning
confidence: 99%
“…1,5,[9][10][11][12][14][15][16]18,20,37,56 To illustrate that the sparse sampling method can capture such marked differences in the respective The response of the average number of interfacial waters, Ñ v φ , to the strength of the linear biasing potential, φ , depends on the hydrophobicity of SAM-water interface. While the response is roughly linear for the hydrophilic OH-terminated SAM surface, it is sigmoidal for the hydrophobic CH 3 -terminated SAM surface.…”
Section: Sam -Water Interfacesmentioning
confidence: 99%
“…[27][28][29][30][31] For example, the fact that P v (N), the probability of observing N water molecules in a small observation volume (v 1 nm 3 ), obeys Gaussian statistics, 3,32 has provided molecular-level insights into the the pressure-induced denaturation of proteins, [33][34][35] as well as the convergence of protein unfolding entropies at a particular temperature. 19,32 Similarly, the LumChandler-Weeks (LCW) theory 5 prediction that P v (N) should develop fat low-N tails for large volumes (v 1 nm 3 ) in bulk water, and near hydrophobic surfaces, 5,15,36 and its verification by simulations, 1,14,18,37 has clarified that water near hydrophobic surfaces is sensitive to perturbations, 18,[38][39][40][41][42][43] and led to the insight that extended hydrophobic surfaces could generically serve as catalysts for the assembly and disassembly of small hydrophobic solutes. 14,44 Importantly, the fact that low-N fluctuations are enhanced near hydrophobic surfaces, also makes them a suitable metric for quantifying the hydrophobicity of a surface, or the strength of its interactions with water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation